Training on making thematic children's masks to create children's independence during the covid-19 pandemic - Musdholifah Musdholifah; Dewie Tri Wijayati; Andre Dwijanto Witjaksono; Ulil Hartono; Achmad Kautsar (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2021)
The use of masks is one way to prevent the spread of the Covid-19 virus. The importance of using these masks has resulted in the need for masks to increase, and items are hard to find in the market. One of the parties who need masks is children. The need for child masks is also experienced by students in the Al-Chusnaini Islamic boarding school in Sidoarjo. The methods used are training and mentoring. The targeted participants are 30 children of the Al Chusnaini Islamic boarding school in Sidoarjo. The training is carried out online, with the resource person providing material via a video uploaded via YouTube. Overall this activity went smoothly, and the enthusiasm of the Al Chusnaini students was also evident. The effectiveness of measured activities according to the data in the discussion section. Hopefully, this activity can be carried out in other places in the future. For the partners, they hope that other materials can be taught to boarding school children so that they have skills outside of school lessons.